Causes of Postpartum Haemorrhage Seen in Patients Referred to Jinnah Postgraduate Medical Center (JPMC) - Nasir, Fatima; Khan, Saba; Simrun; Zehra, Tamkeen; Kashaf, Memoona; Nasir, Aisha (Indus Journal of Bioscience Research, 2025)
Background and Aim: Postpartum hemorrhage (PPH) remains an important contributor to maternal illness and mortality, especially in developing countries. Prompt identity of its causes is necessary for timely management and improvement in maternal outcomes. Therefore, the present study aimed to determine the causes of postpartum hemorrhage in patients referred to Jinnah Postgraduate Medical Centre, Karachi. Patients and Methods: This cross-sectional study investigated 104 postpartum hemorrhage (primary or secondary) cases in the Obstetrics and Gynecology Department, Jinnah Postgraduate Medical Centre (JPMC), Karachi from March 2024 to March 2025. Patients referred from peripheral healthcare facilities either booked or unbooked cases, preterm and term deliveries, and inpatients were included. Data obtained from medical records, including demographic variables (age, marital status, parity, booking status), obstetrical history (gestational age, mode of delivery), type of PPH (primary or secondary), and specific causes (e.g., uterine atony, trauma, uterine rupture, placenta accreta spectrum, infection, uterine inversion, arteriovenous malformation, and coagulation disorders). SPSS version 26 used for data analysis. Results: The current study included 104 patients with postpartum hemorrhage; the most affected age group was 21–30 years 48 (46.2%) cases. The incidence of primary and secondary PPH was 96 (92.3%) and 8 (7.7%), respectively. Anemia was the most prevalent risk factor found in 26 (25%) cases followed by Prolonged Labor 12 (11.5%) and Eclampsia 8 (7.7%) cases. Atonic uterus emerged as the most prevalent cause of PPH, accounting for 73 (70.2%) cases. Traumatic PPH contributed to 20 (19.2%) cases and retained product of conception (RPOC) 11 (10.6%) cases. Of the total cases, 44 (42.3%) patients underwent surgical intervention whereas 60 (57.7%) were medically managed. Conclusion: Atonic uterus, identified as a major cause of postpartum hemorrhage (PPH), followed by traumatic and retained products of conception. These findings emphasize the need of prompt recognition and management of the atonic uterus, as well as effectively reducing the incidents and severity of PPH for trauma and incomplete placental expulsion.